Neisseria gonorrhea in Ethiopia, prevalence among STI suspected patients and its antimicrobial susceptibility: a systematic review and meta-analysis - Gobezie, Mengistie Yirsaw; Tesfaye, Nuhamin Alemayehu; Solomon, Tewodros; Demessie, Mulat Belete; Kassa, Tesfaye Dessale; Wendie, Teklehaimanot Fentie; Alemayehu, Ermiyas; Hassen, Minimize (Frontiers in Microbiology, 2024)
Introduction: Neisseria gonorrhea (N. gonorrhea) represents a significant causative agent of sexually transmitted infections (STIs), posing considerable global health challenges. Despite the presence of diagnostic tools and empirically guided therapies, the escalating AMR of N. gonorrhea continues to pose a threat. This study aims to assess the prevalence of N. gonorrhea among STI suspected patients in Ethiopia and explore the patterns of AMR to common antimicrobials. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a systematic review and meta-analysis. A thorough search of electronic databases from July 11 to July 24, 2023, identified ten eligible studies. Data were extracted and analyzed using a random-effects model. Heterogeneity was assessed using the I² statistic, and publication bias was evaluated through Egger's regression test and funnel plots. Results: The overall pooled prevalence of N. gonorrhea among STI suspected patients in Ethiopia was 20% (95% confidence interval (CI): 8-30, I² = 99.0%; p-value < 0.001). Substantial regional variations were observed, with the highest prevalence in Addis Ababa (55%, 95% CI: 45-65) and the lowest in the Southern Nations, Nationalities, and Peoples' Region (SNNPR) (4%, 95% CI: 2-8). The pooled prevalence of AMR to ciprofloxacin, ceftriaxone, azithromycin, benzylpenicillin, tetracycline, and spectinomycin was 37%, 9%, 10%, 79%, 93%, and 2%, respectively. Significant heterogeneity existed between studies (I² = 99.0%; p value < 0.001). Publication bias, identified through funnel plot examination and Egger's regression test (p < 0.001), execution of trim and fill analysis resulted in an adjusted pooled prevalence of (6.2%, 95% CI: -6.8-19.3). Conclusion: The prevalence of N. gonorrhea among STI suspected patients in Ethiopia is alarming, particularly in specific regions. The elevated AMR to ciprofloxacin underscores the immediate need for alternative treatment options and enhanced surveillance systems. Future initiatives should prioritize strengthening laboratory capacities and implementing targeted interventions to curtail N. gonorrhea transmission and prevent the emergence of AMR.